"Such a Powerful Tool":Testing, Business Interests and School Segregation in North Carolina, 1970s-1990s - Esther Cyna (Les éditions de la Maison des sciences de l'Homme, 2020)
How did standardized testing become the cornerstone of U.S. education policy at the end of the 20th century? This article examines how, why, and to what extent the shift to outcomes-based reform played out at the state and local levels from the early 1970s to the late 1990s in North Carolina. It looks closely at the relationship between a growing emphasis on educational outcomes and the involvement of business interest groups, and the implications of this movement for patterns of school segregation in the state. Borrowing language and discourse from the business world, a new performance paradigm increasingly dominated education policy in a state that has historically been a forerunner in testing reform. Drawing on archival research on the federal, state, county and district scales, this article shows how North Carolina's educational agenda evolved from 1970s to 1990s and interacted with patterns of segregation in the state, and how policy was implemented, received, and sometimes contested in a redefined landscape.